Laugh Your Way Back to Democracy: Thailand’s ‘Red Sunday’ group and humorous nonviolent actions - Sombatpoonsiri, Janjira (Journal of Human Rights and Peace Studies, 2015)
This article seeks to analyze the impact humorous nonviolent actions had on a social movement operating under repressive circumstances. The focus rests upon Thailand’s Red Sunday group which emerged after the 2010 military crackdown. The group showed that humorous nonviolent actions could induce two political advantages: disarming of the opponent and disarming of the movement itself. Playful nonviolent tactics enable protesters’ avoidance of possible arrests by creating a crisis of legitimacy for the authorities. For the movement’s members, humor helped them to achieve self-reflection, encouraging a positive outlook of where nonviolent options were available they were creative enough. The Thai case resonates with the experiences of social movements in many societies where humor contributed to overcoming fear and creating hope.